Fabrication and Aging Behaviour of In-Situ Aluminum Composites - Erarslan, Yaman (CARL HANSER VERLAG, 2011)
Commonly applied in situ procedures with the aim of producing alumina particles or whiskers include the reactions between a metal oxide and aluminum. The metal, reduced with the alumina formation reaction, afterwards generally reacts with Al and transforms into an intermetallic form which will act as a reinforcing member in the composition of the matrix. In this study, by adding CuO powder in ratios of 5, 10 and 15 wt.-% composite billets were produced by the in situ procedure of stir casting. XRD patterns and microstructures of the produced Al-Al2O3 composites were examined by using optical and electron microscopy (SEM). Following the homogenization procedure on the composite material, hot deformation and thermal aging procedures were applied. The changes in the mechanical properties were compared with commercially pure Aluminum.
Keywords: MECHANICAL-PROPERTIES; MICROSTRUCTURE; CARBIDE; Materials Science